2012
DOI: 10.1103/physrevd.86.113003
|View full text |Cite
|
Sign up to set email alerts
|

A supersymmetricSU(5)×Tunified model of flavor with largeθ13

Abstract: We present a SUSY SUð5Þ Â T 0 unified flavor model with type I seesaw mechanism of neutrino mass generation, which predicts the reactor neutrino angle to be 13 % 0:14 close to the recent results from the Daya Bay and RENO experiments. The model predicts also values of the solar and atmospheric neutrino mixing angles, which are compatible with the existing data. The T 0 breaking leads to tribimaximal mixing in the neutrino sector, which is perturbed by sizeable corrections from the charged lepton sector. The mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 65 publications
4
83
0
Order By: Relevance
“…The goal would then be to include a mechanism that raises the predicted value of θ 13 , which is the subject of this letter. Such efforts have been considered before; in a different SU (5) × T GUT model it has been demonstrated that one can preserve TBM in the neutrino sector by modifying the mixing in the charged lepton sector to generate an appropriate θ 13 [29]. In this letter, we take a different approach and introduce one more singlet scalar field coupling to the neutrino sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal would then be to include a mechanism that raises the predicted value of θ 13 , which is the subject of this letter. Such efforts have been considered before; in a different SU (5) × T GUT model it has been demonstrated that one can preserve TBM in the neutrino sector by modifying the mixing in the charged lepton sector to generate an appropriate θ 13 [29]. In this letter, we take a different approach and introduce one more singlet scalar field coupling to the neutrino sector.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the discovery of a large θ 13 , various models based on discrete family symmetries, such as A 4 [24][25][26][27], S 4 [28], T [29] and A 5 [30] have been revisited lately, and more examples can be found in the review [31]. It has been pointed out [32] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, new Clebsch-Gordan (CG) factors appear as Yukawa coupling ratios, with interesting associated implications for the masses and mixing of the fermions, cf. [12,13] and [14][15][16][17]. The main goal of this paper is to show how GUT flavour models featuring these promising quark-lepton mass relations can be combined with a version of the DMPM for solving the DTS problem.…”
Section: Jhep09(2014)141mentioning
confidence: 99%
“…[15][16][17]. By introducing pairs of heavy messengers in the SU(5) representations R andR, the renormalizable couplings associated with the effective operators are specified and a unique contraction of SU (5) indices of the effective operator is obtained simply by integrating out the messenger fields.…”
Section: Yukawa Coupling Ratiosmentioning
confidence: 99%
“…The interplay between flavor symmetries and CP symmetries has been generally discussed in [40,41]. In addition, there are other theoretical approaches involving both family symmetry and CP violation [42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Jhep12(2014)007mentioning
confidence: 99%